Manajemen Anestesi Pasien dengan Low Ejection Fraction yang Menjalani Operasi Tumor Ovarium - Pratomo, Bhirowo Yudo; Kurniawaty, Juni; Sari, Dhanty Dwita (Jurnal Komplikasi Anestesi, 2022)
Anesthetic management of patients with dilated cardiomyopathy (DCM) is a challenge to the anesthesiologist, due to poor left systolic function, ventricular enlargement, risk of malignant arrhythmias and sudden cardiac death. Therefore, preoperative assessment and appropriate anesthetic management are important in patients with DCM. Patients with a low EF <35% may be at risk for life-threatening irregular heart rhythms. Any arrhythmia in these patients requires immediate treatment because otherwise it can lead to sudden cardiac arrest and sudden death. In summary, the optimal anesthetic management of patients with dilated cardiomy- opathy requires good preoperative assessment, close perioperative monitoring, suitable anesthetic, optimization fluid management, and stable hemodynamic status.